Preparation method of carbon dot nano-enzyme based on response surface methodology optimization, carbon dot nano-enzyme and application of carbon dot nano-enzyme

Optimizing the preparation of carbon dot nanoenzymes by responding to the surface method, the problems of waste of resources and low efficiency in traditional methods are solved, and high-performance carbon dot nanoenzymes are effectively prepared, which improves its application capabilities in environmental monitoring.

CN119240666AActive Publication Date: 2025-01-03UNIV OF JINAN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411326812.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Traditional methods waste resources, environmental impact and synthesis efficiency when preparing carbon dot nanoenzymes, making it difficult to control and efficiently prepare high-performance carbon dot nanoenzymes, which limits its application in environmental monitoring and other fields.

Method used

采用响应面法优化碳点纳米酶的制备方法,通过水热反应和纯化过程,结合葡萄糖、硫酸亚铁和浓硫酸,优化反应条件以提高碳点纳米酶的荧光强度,利用回归方程确定最佳 Preparation parameters.

Benefits of technology

The efficient preparation of carbon dot nanoenzymes was achieved, high fluorescence quantum yield and excellent peroxidase-like activity were obtained, and the sensitivity and accuracy of tetracycline detection was improved, resource waste wasted, and research cycles were shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240666A_ABST
    Figure CN119240666A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon dot nano-enzyme based on response surface methodology optimization, the carbon dot nano-enzyme and application of the carbon dot nano-enzyme, and belongs to the technical field of carbon dot nano-enzyme preparation. The preparation method provided by the invention comprises the following steps: stirring and dissolving glucose, ferrous sulfate and concentrated sulfuric acid in water, then carrying out hydrothermal reaction, and after the reaction is finished, purifying to obtain carbon dot nano-enzyme; determining the fluorescence intensity of the carbon dot nano-enzyme; selecting the molar ratio of glucose to ferrous sulfate, the addition amount of concentrated sulfuric acid and the reaction time as influence factors, and taking the fluorescence intensity of the carbon dot nano-enzyme as an inspection value, and performing response surface method optimization to obtain a regression equation; and finally, optimal reaction conditions are obtained through software optimization. The synthesis efficiency is high, and the optimally synthesized carbon dot nano-enzyme has high fluorescence quantum yield and excellent peroxidase-like activity, can be applied to tetracycline detection as a colorimetric probe, and is high in detection sensitivity and accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dot nanozyme preparation, and in particular to a preparation method of carbon dot nanozyme optimized based on response surface methodology, carbon dot nanozyme and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As a new type of pollutants, medicines and personal care products, if they exist in the environment for a long time, will pose a serious threat to the health of microorganisms, animals and plants. Therefore, it is of certain research significance to detect and analyze new pollutants in the environment. Traditional pollutant detection methods require the use of expensive instruments and complex operations. In recent years, with the rapid development of nanotechnology, carbon dot nanozymes, as a new type of nanomaterial, have gained wide attention in the fields of bioimaging, sensors and environmental monitoring due to their unique optical properties, good biocompatibility and easy preparation.

[0004] Researchers have used hydrothermal, microwave-assisted, electrochemical and other methods to prepare carbon dot nanozymes in order to obtain carbon dot nanozymes with excellent properties. However, most of them use artificial experience-driven trial-and-error methods, which leads to resource waste, environmental impact, low synthesis efficiency and other problems, which are not conducive to sustainable development. At present, how to controllably and efficiently prepare carbon dot nanozymes is still a considerable challenge. Summary of the invention

[0005] In view of this, the present invention provides a preparation method of carbon dot nanozyme, carbon dot nanozyme and application thereof based on response surface methodology optimization. The present invention can quickly and efficiently optimize the preparation conditions of carbon dot nanozyme, and at the same time can obtain high-performance carbon dot nanozyme, which can be used as a probe to analyze new pollution in the detection environment.

[0006] In a first aspect, the present invention provides a method for preparing carbon dot nanozymes optimized based on response surface methodology, comprising the following steps:

[0007] Glucose, ferrous sulfate and concentrated sulfuric acid are stirred and dissolved in water, and then a hydrothermal reaction is carried out. After the reaction is completed, the carbon dot nanozyme is obtained by purification; and the fluorescence intensity of the carbon dot nanozyme is measured;

[0008] The molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were selected as influencing factors, and the fluorescence intensity of the carbon dot nanozyme was used as the observation value. The response surface method was used for optimization and the regression equation was obtained.

[0009] Finally, the maximum fluorescence intensity of the carbon dot nanozyme and the corresponding molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were obtained through software optimization.

[0010] Preferably, the regression equation is as follows:

[0011] Y=2.08×10 5 +10.63A-34622.5B+1.22×10 5 C+812.25AB+32007.5AC+12704.75B

[0012] C+44001.6A 2 -9534.15B 2 +1.11×10 5 C 2 .

[0013] Preferably, the molar ratio of glucose to ferrous sulfate is 1 to 3, the amount of concentrated sulfuric acid added is 0.2 to 0.6 vol% of the amount of water added, and the reaction time is 8 to 12 hours.

[0014] Furthermore, the molar ratio of glucose to ferrous sulfate is 3, the amount of concentrated sulfuric acid added is 0.52 vol% of the amount of water added, and the reaction time is 12 h.

[0015] Preferably, the temperature of the hydrothermal reaction is 150-250°C.

[0016] Preferably, the usage ratio of ferrous sulfate to water is (0.2-2) g:50 mL.

[0017] Preferably, the purification step is specifically as follows: centrifuging the product after the hydrothermal reaction, dialyzing the supernatant, and drying the dialysate to obtain the carbon dot nanozyme.

[0018] Preferably, the step of determining the fluorescence intensity of the carbon dot nanozyme is specifically as follows: dissolving the carbon dot nanozyme in a solvent to obtain a carbon dot nanozyme solution, fixing the excitation wavelength to 370-450nm, performing fluorescence spectrum detection on the carbon dot nanozyme solution, and recording the intensity of the maximum fluorescence emission peak.

[0019] In a second aspect, the present invention provides the carbon dot nanozyme prepared by the above preparation method.

[0020] In a third aspect, the present invention provides the application of the above-mentioned carbon dot nanozyme in tetracycline detection.

[0021] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0022] (1) The present invention uses glucose as a carbon source, ferrous sulfate as a metal precursor, and concentrated sulfuric acid as an additive to prepare S, Fe-doped carbon dot nanozymes through a hydrothermal synthesis method. At the same time, the response surface methodology is used to establish the relationship between the reaction conditions and the fluorescence intensity of the carbon dot nanozymes, and the optimal reaction conditions are optimized. It has the advantages of controllable and efficient, high synthesis efficiency, and avoids waste of resources;

[0023] (2) The carbon dot nanozyme optimized and synthesized by the present invention has high fluorescence quantum yield, excellent peroxidase-like activity and good catalytic activity, and can be used as a colorimetric probe for the detection of tetracycline with high detection sensitivity and accuracy. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 is a correlation analysis diagram of the predicted value and the experimental value of Example 1 of the present invention;

[0026] Figure 2 is a response surface diagram of the effect of the interaction between the molar ratio of glucose to ferrous sulfate and the content of concentrated sulfuric acid on the fluorescence intensity in Example 1 of the present invention;

[0027] Figure 3 is a response surface diagram of the effect of the interaction between the molar ratio of glucose to ferrous sulfate and the reaction time on the fluorescence intensity in Example 1 of the present invention;

[0028] Figure 4 is a response surface diagram of the effect of the interaction between the concentrated sulfuric acid content and the reaction time on the fluorescence intensity in Example 1 of the present invention;

[0029] Figure 5 This is a transmission electron microscopy image of the S, Fe-doped carbon dot nanozyme prepared under the optimal conditions in Example 1 of the present invention;

[0030] Figure 6 It is the UV-visible absorption, fluorescence excitation and fluorescence emission curves of the S,Fe doped carbon dot nanozyme prepared under the optimal conditions in Example 1 of the present invention;

[0031] Figure 7 This is a diagram showing the enzyme activity test results of the S, Fe-doped carbon dot nanozyme prepared under the optimal conditions in Example 1 of the present invention;

[0032] Figure 8The present invention uses the Michaelis-Menten equation to fit the steady-state kinetic curves with o-PD and H2O2 as substrates, wherein a is the steady-state kinetic curve with o-PD as substrate, and b is the steady-state kinetic curve with H2O2 as substrate;

[0033] Fig. 9 It is a curve diagram showing the relationship between the change in absorbance and the concentration of tetracycline in the present invention. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0035] The present invention provides a method for preparing carbon dot nanozymes optimized based on response surface methodology, comprising the following steps:

[0036] Stirring and dissolving glucose, ferrous sulfate and concentrated sulfuric acid in water, and then subjecting to a hydrothermal reaction, after the hydrothermal reaction, purifying to obtain the carbon dot nanozyme; measuring the fluorescence intensity of the carbon dot nanozyme;

[0037] The molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were selected as influencing factors, and the fluorescence intensity of the carbon dot nanozyme was used as the observation value. The response surface method was used for optimization and the regression equation was obtained.

[0038] Finally, the maximum fluorescence intensity of the carbon dot nanozyme and the corresponding molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were obtained through software optimization.

[0039] The present invention uses glucose as a carbon source, ferrous sulfate as a metal precursor, and concentrated sulfuric acid as an additive, and prepares S, Fe doped carbon dot nanozymes by hydrothermal synthesis, and simultaneously uses the response surface method to establish the relationship between reaction conditions and carbon dot nanozyme fluorescence intensity, and optimizes and obtains the optimal reaction conditions. The response surface method is an analytical method for comprehensively processing the relationship between experimental variables and response values ​​using statistics, including designing experimental optimization schemes, analytical processing, multidimensional modeling, etc., and its principle is to arrange the design experimental scheme according to the Box-Benhnken central composite experimental design, and consider random errors on this basis, and the complex unknown implicit function relationship between variables and response values ​​is expressed in a small area with a multivariate quadratic regression equation, and a second-order polynomial relationship is used, and the result presents a multidimensional image, which is intuitive and simple. Therefore, the present invention can quickly and efficiently determine the optimal preparation conditions of carbon dot nanozymes, shorten the research cycle, and avoid causing waste of resources.

[0040] In the present invention, the regression equation is as follows:

[0041] Y=2.08×10 5 +10.63A-34622.5B+1.22×10 5 C+812.25AB+32007.5AC+12704.75B

[0042] C+44001.6A 2 -9534.15B 2 +1.11×10 5 C 2 Among them, Y is the fluorescence intensity of carbon dot nanozyme, A is the molar ratio of glucose to ferrous sulfate, B is the amount of concentrated sulfuric acid added, and C is the reaction time.

[0043] In the present invention, the molar ratio of glucose to ferrous sulfate is 1 to 3, the amount of concentrated sulfuric acid added is 0.2 to 0.6 vol% of the amount of water added, and the reaction time is 8 to 12 h. Through optimization, the optimal molar ratio of glucose to ferrous sulfate is 3, the optimal amount of concentrated sulfuric acid added is 0.52 vol% of the amount of water added, and the optimal reaction time is 12 h.

[0044] In the present invention, the temperature of the hydrothermal reaction is 150-250° C., more preferably 180-220° C., and most preferably 200° C. The present invention does not impose any particular restrictions on the specific steps of the hydrothermal reaction process, and the hydrothermal reaction process commonly used in the art can be used.

[0045] In the present invention, the usage ratio of ferrous sulfate to water is (0.2-2) g:50 mL, more preferably (0.2-0.8) g:50 mL.

[0046] In the present invention, the purification step is specifically: centrifuging the product after the hydrothermal reaction, then dialyzing the supernatant, and drying the dialyzate to obtain the carbon dot nanozyme. The present invention does not specifically limit the specific centrifugation, dialysis and drying processes, and the centrifugation, dialysis and drying steps commonly used in the art can be used.

[0047] In the present invention, the step of determining the fluorescence intensity of the carbon dot nanozyme is specifically as follows: dissolving the carbon dot nanozyme in a solvent to obtain a carbon dot nanozyme solution, fixing the excitation wavelength to 370 to 450 nm, performing fluorescence spectrum detection on the carbon dot nanozyme solution, and recording the intensity of the maximum fluorescence emission peak. The present invention does not impose any particular restriction on the specific solvent type, as long as it can dissolve the carbon dot nanozyme.

[0048] The present invention also provides the carbon dot nanozyme prepared by the above preparation method. The carbon dot nanozyme obtained by optimizing the reaction conditions by response surface methodology has high fluorescence quantum yield, excellent peroxidase-like activity and good catalytic activity.

[0049] The present invention also provides the application of the above-mentioned carbon dot nanozyme in tetracycline detection. The carbon dot nanozyme prepared by the present invention has excellent detection sensitivity and accuracy when applied to tetracycline detection. The present invention does not impose any special restrictions on the specific application process, and the application method commonly used in the art can be used.

[0050] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0051] Example 1

[0052] 1. Preparation process of S,Fe-doped CDs nano-enzyme:

[0053] Glucose, 0.5 g ferrous sulfate (0.0018 mol) and concentrated sulfuric acid were added to a beaker containing 50 mL of distilled water, stirred until completely dissolved, and then transferred to a polytetrafluoroethylene-lined stainless steel reactor, and reacted at 200 ° C in a blast drying oven for a set time. After the reaction was completed, it was naturally cooled to room temperature, centrifuged at high speed to obtain the supernatant, dialyzed for 24 hours, and the dialyzate was freeze-dried to obtain carbon dot nanozymes under different conditions.

[0054] Fluorescence intensity detection of carbon dot nanozyme: 0.005 g of the carbon dot nanozyme prepared above was dissolved in 5 mL of ethanol and ultrasonicated for 1 min to obtain a uniform solution; at 25°C, the excitation wavelength was fixed at 370-450 nm, the solution was subjected to fluorescence spectrum detection, and the intensity of the maximum fluorescence emission peak was recorded.

[0055] 2. Optimization process of preparation method of S, Fe doped carbon dot nanozymes:

[0056] Traditionally, obtaining high-performance carbon dot nanozymes requires screening of the preparation precursors and precise control of the preparation conditions. In this example, the preparation conditions of carbon dot nanozymes were optimized using the BBD model (Box-Behnken Design). The Design-Expert.V8.0.6 software was used to optimize the preparation conditions of the carbon dot nanozymes. G :n Fe ), concentrated sulfuric acid content (factor B) and reaction time (factor C, Time) are three factors as input variables, which are input in the Box-Behnken Design interface. The Response output value is fluorescence intensity. The required experimental process design can be obtained through simulation. The experimental process design is shown in Table 1.

[0057] Table 1 Experimental process design based on response surface methodology (Box-Behnken)

[0058]

[0059] According to the model design, the experiment was carried out 17 times. The fluorescence intensity of S and Fe doped carbon dot nanozymes prepared under different conditions is shown in Table 2. Determination coefficient R 2 and the adjusted R 2 The values ​​are 0.9195 and 0.8161 respectively, and the predicted R 2 The value of the F and P values ​​of the model significance test were 8.89 and 0.0044 (P<0.005), respectively, indicating that the model was very significant and could be used for analysis. The missing fit of the F and P values ​​was 3.65 and 0.23 (p>0.05), respectively, indicating that the model had little difference with the experiment and could be analyzed by regression equation.

[0060] Table 2 Fluorescence intensity changes based on Box-Behnken experimental design

[0061]

[0062] Through model fitting, the binomial equilibrium equation of the fluorescence intensity Y of the prepared carbon dot nanozyme and the experimental factors can be obtained, as shown in the following equation:

[0063] Y=2.08×10 5 +10.63A-34622.5B+1.22×10 5 C+812.25AB+32007.5AC+12704.75B

[0064] C+44001.6A 2 -9534.15B 2 +1.11×10 5 C 2 ;

[0065] Wherein, A represents the molar ratio of glucose to ferrous sulfate, B represents the content of concentrated sulfuric acid, and C represents the reaction time. Figure 1 It can be seen that the experimental results have a good correlation with the predicted values, such as Figure 1 shown.

[0066] The interactive effects among the molar ratio of glucose to ferrous sulfate, the content of concentrated sulfuric acid and the reaction time were further analyzed. Figure 2 The effect of the interaction between the molar ratio of glucose to ferrous sulfate and the content of concentrated sulfuric acid on the fluorescence intensity is shown. Figure 2 It can be seen that the effect of H2SO4 on fluorescence intensity is greater than the molar ratio of glucose to ferrous sulfate. With the increase of H2SO4 content, the fluorescence intensity first increases and then decreases. Figure 3 The effect of the interaction between the molar ratio of glucose to ferrous sulfate and the reaction time on the fluorescence intensity is shown. Figure 3 It can be seen that the fluorescence intensity increases with the increase of reaction time and the molar ratio of glucose to ferrous sulfate, and the effect of reaction time is more obvious. Figure 4 The effect of the interaction between the concentration of sulfuric acid and the reaction time on the fluorescence intensity is shown. Figure 4 It can be seen that with the increase of sulfuric acid content, the fluorescence intensity of the prepared nanozyme first increases and then decreases; with the increase of reaction time, the fluorescence intensity of the nanozyme gradually increases, and the influence of reaction time is more obvious.

[0067] According to the results, the influence of the fluorescence intensity is as follows: factor C (reaction time) > factor B (H2SO4 content) > factor A (glucose to ferrous sulfate molar ratio), which is consistent with the model prediction (F values ​​are 41.72, 3.37, and 3.175×10 -7 ). Based on the model optimization, the optimal preparation conditions were determined: A: glucose to ferrous sulfate molar ratio = 3; B: H2SO4 content = 0.26mL (i.e., the volume fraction relative to solvent water is 0.52%); C: reaction time is 12h. Under this optimal condition, S, Fe doped carbon dot nanozymes were prepared and used in subsequent detection, analysis and application processes.

[0068] Test example

[0069] 1. Transmission electron microscopy (TEM) analysis:

[0070] The structure and particle size of the prepared S,Fe doped carbon dot nanozymes were analyzed by transmission electron microscopy (TEM). Figure 5 As shown in the figure, it can be seen that the prepared S, Fe doped carbon dot nanozymes are evenly distributed, and their lattice size is about 0.21nm, which is consistent with the (100) lattice distance of graphite carbon. Measured by Nano Measurer 1.2software, its particle size is about 3-6nm.

[0071] 2. Optical property analysis:

[0072] Figure 6 The UV-visible absorption, fluorescence excitation and fluorescence emission curves of S, Fe doped carbon dot nanozymes prepared under optimal conditions. It can be seen from the figure that S, Fe doped carbon dot nanozymes have a wide absorption band in the range of 220-400nm. The optimal excitation wavelength is 366nm and the optimal emission wavelength is 440nm. The fluorescence quantum yield of S, Fe doped carbon dot nanozymes is calculated to be 50.14%.

[0073] 3. Enzyme activity evaluation:

[0074] Using o-phenylenediamine (o-PD) as substrate, the enzyme activity of the prepared S,Fe-doped CDs nanoenzyme was evaluated. Figure 7 As shown in the figure, S,Fe doped carbon dot nanozymes can promote the oxidation of o-PD to generate brown oxidized o-PD in the presence of H2O2, and an obvious absorption peak appears at 450nm. However, in different systems such as S,Fe doped carbon dot nanozymes, o-PD, H2O2, o-PD+H2O2, S,Fe doped carbon dot nanozymes+o-PD, S,Fe doped carbon dot nanozymes+H2O2, no absorption peak appears at 450nm, which further proves that S,Fe doped carbon dot nanozymes have excellent peroxidase-like activity.

[0075] To further evaluate the activity of S, Fe-doped carbon dot nanozymes, under the optimal reaction conditions, o-PD and H2O2 were used as substrates and the steady-state kinetic analysis method was used. According to the Michaelis-Menten equation, the Michaelis-Menten curves related to o-PD and H2O2 can be obtained. Figure 8 It can be seen from a and b in the figure that the reaction rate of the system increases linearly with the increase of H2O2 and o-PD concentrations, and gradually reaches equilibrium after the concentration exceeds a certain range, indicating that the enzyme catalysis reaction of S, Fe doped carbon dot nanozymes conforms to the Michaelis-Menten model. According to the fitting calculation, with o-PD as the substrate, K m and V m 2.85 mM and 36 × 10 -8 M.s -1 ; When H2O2 is used as substrate, K m and V m 0.27mM and 5.61×10-8M·s -1 . By comparing with the K m and V m By comparison, the S, Fe-doped carbon dot nanozymes prepared in this application have good catalytic activity.

[0076] Application Examples

[0077] In order to further verify the usability of S, Fe doped carbon dot nanozymes, this application example constructed a S, Fe doped carbon dot nanozyme colorimetric probe to detect tetracycline. The specific method is as follows:

[0078] The prepared carbon dot nanozyme was mixed with the tetracycline hydrochloride sample and allowed to react fully. During the reaction, the tetracycline molecules combined with the functional groups on the surface of the carbon dot nanozyme, resulting in changes in the catalytic activity of the carbon dot nanozyme. The absorbance of the oxidized substrate (ox-oPD) after the reaction was measured using a UV-visible spectrometer at 450nm. Based on the relationship between the change in absorbance and the concentration of tetracycline (TC), a standard curve was established, such as Fig. 9 As shown in the figure, as the concentration of tetracycline increases, the absorbance gradually increases. Through the fitting analysis of absorbance and tetracycline concentration, it has a high credibility in the range of 6-100μg / mL, and its R 2 =0.9902.

[0079] The practical applicability of the established probe was further investigated, and the content of tetracycline in actual aquaculture wastewater samples was analyzed. The measured experimental content is shown in Table 3. It can be seen that the recovery rate is 103.22%-110.31%, and RSD<6%, indicating that the constructed colorimetric probe has high sensitivity and accuracy in detecting actual samples.

[0080] Table 3 Evaluation of the performance of the constructed probe by aquaculture wastewater samples

[0081]

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing carbon dot nanozymes optimized based on response surface methodology, characterized in that: The steps include: Glucose, ferrous sulfate and concentrated sulfuric acid are stirred and dissolved in water, and then a hydrothermal reaction is carried out. After the reaction is completed, the carbon dot nanozyme is obtained by purification; and the fluorescence intensity of the carbon dot nanozyme is measured; The molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were selected as influencing factors, and the fluorescence intensity of the carbon dot nanozyme was used as the observation value. The response surface method was used for optimization and the regression equation was obtained. Finally, the maximum fluorescence intensity of the carbon dot nanozyme and the corresponding molar ratio of glucose to ferrous sulfate, the amount of concentrated sulfuric acid added and the reaction time were obtained through software optimization.

2. The preparation method according to claim 1, characterized in that The regression equation is as follows: <h2 style=";text-align:left;direction:ltr">Y = 2.08×10<h2 style=";text-align:left;direction:ltr"> 5 <h2 style=";text-align:left;direction:ltr"> +10.63A-34622.5B+1.22×10<h2 style=";text-align:left;direction:ltr"> 5 <h2 style=";text-align:left;direction:ltr"> C+812.25AB+32007.5AC+12704.75B C+44001.6A 2 -9534.15B 2 +1.11×10 5 C 2 。 3. The preparation method according to claim 1, characterized in that: The molar ratio of glucose to ferrous sulfate is 1 to 3, the amount of concentrated sulfuric acid added is 0.2 to 0.6 vol% of the amount of water added, and the reaction time is 8 to 12 hours.

4. The preparation method according to claim 3, characterized in that: The molar ratio of glucose to ferrous sulfate is 3, the amount of concentrated sulfuric acid added is 0.52 vol% of the amount of water added, and the reaction time is 12 h.

5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150-250°C.

6. The preparation method according to claim 1, characterized in that: The dosage ratio of the ferrous sulfate to water is (0.2-2) g:50 mL.

7. The preparation method according to claim 1, characterized in that: The purification step is specifically as follows: centrifuging the product after the hydrothermal reaction, dialyzing the supernatant, and drying the dialyzate to obtain the carbon dot nanozyme.

8. The preparation method according to claim 1, characterized in that: The step of determining the fluorescence intensity of the carbon dot nanozyme is specifically as follows: dissolving the carbon dot nanozyme in a solvent to obtain a carbon dot nanozyme solution, fixing the excitation wavelength to 370-450nm, performing fluorescence spectrum detection on the carbon dot nanozyme solution, and recording the intensity of the maximum fluorescence emission peak.

9. The carbon dot nanozyme prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon dot nanozyme as claimed in claim 9 in tetracycline detection.

Citation Information

Patent Citations

  • Hydrothermal preparation method of carbon quantum dot used as visible light catalytic photosensitizer

    CN107099287A

  • Carbon quantum dot for detecting activity of inulinase and preparation method and application of carbon quantum dot

    CN108562564A

  • Preparation method and application of nano-enzyme for colorimetric detection of glucose

    CN113295685A

  • Alpha-amanita peptide detection method based on carbon dot gold nano enzyme

    CN115656080A

  • Preparation method of iron monatomic doped fluorescent carbon dot nano-enzyme

    CN115920890A